MMS22L Expression as a Predictive Biomarker for the Efficacy of Neoadjuvant Chemoradiotherapy in Oesophageal Squamous Cell Carcinoma - Luo, Qiyu; He, Wenwu; Mao, Tianqin; Leng, Xuefeng; Wu, Hong; Li, Wen; Deng, Xuyang; Zhao, Tingci; Shi, Ming; Xu, Chuan; Han, Yongtao (Frontiers in Oncology, 2021)
Long-term survival in esophageal squamous cell carcinoma (ESCC) is related with pathological response after neoadjuvant chemoradiotherapy (NCRT) followed by surgery. However, effective biomarkers for prediction of pathologic response were still lacking. Therefore, a systematic analysis focusing on genes associated with efficacy of chemoradiotherapy in ESCC will provide valuable insights into the regulation of molecular processes. By screening publications deposited in PubMed， We collected genes associated with efficacy of chemoradiotherapy. A specific subnetwork was constructed using Steiner minimum tree algorithm. Survival analysis in Kaplan-Meier Plotter online resources was performed to explore the relationship between gene mRNA expression and prognosis of patients with ESCC. Quantitative real-time polymerase chain reaction (qRT-PCR), Western blotting and Immunohistochemical staining (IHC) were used to evaluate the key gene expression. The areas under the receiver operating characteristic (ROC) curves (AUCs) were used to describe performance and accuracy. Transwell assays assessed cell migration and Cell viability was detected by CCK8 assay. Finally, we identified 101 genes associated with efficacy of chemoradiotherapy. Moreover, specific molecular network included some potential related genes, such as CUL3, MUC13, MMS22L, MME, UBC, VAPA, CYP1B1 and UGDH. MMS22L mRNA expression level had most significant association with the ESCC patient outcome (P<0.01). Furthermore, MMS22L was downregulated at both the mRNA (P <0.01) and protein levels in tumor tissues compared with normal tissues. Lymph node metastasis was significantly associated with low MMS22L expression (P <0.001). MMS22L levels were inversely correlated with NCRT response in ESCC (P <0.01). The resulting area under the ROC curve was 0.847 (95% CI: 0.7232 to 0.9703; P< 0.01). Clearly, low MMS22L expression could be an effective predictive biomarker for resistance to NCRT in ESCC.